The effect of subcutaneous injection duration on patients receiving low-molecular-weight heparin: Evidence from a systematic review - Li-juan Yi; Ting Shuai; Xu Tian; Zi Zeng; Li Ma; Guo-min Song (Elsevier, 2016)
To assess the effect of the injection duration of subcutaneous low-molecular-weight heparin (LMWH) on pain and bruising in patients. Randomized controlled trials and quasi-experimental studies were searched for in four electronic databases. The pooled effect size was expressed as relative risk (RR) and mean difference (MD) with 95% confidence intervals (CI) for dichotomous and continuous data. Cochrane Q and p value were used to assess heterogeneity and the I2 statistic was adopted to quantify the level. Finally, eight studies involving a total of 532 participants met our inclusion criteria. The slow (30 second) injection was associated with a reduction in pain intensity and duration, and lower bruising occurrence at 48-72 hours and 48 hours post injection. The bruising area was also smaller at 48 hours and 60 hours post injection. No differences were identified between the slow and fast (10 second) injection in bruising area and bruising occurrence at 24 hours and 60 hours post injection. With present evidences, slow injection of LMWH is beneficial to the patient's well being, but further studies to identify the feasibility and standardization of the technique is recommended. Keywords: Heparin, Injections,subcutaneous, Injection duration, Systematic review, Meta-analysis